Toward a Differential and Situated View of Assessment Literacy: Studying Teachers' Responses to Classroom Assessment Scenarios - DeLuca, Christopher; Coombs, Andrew; MacGregor, Stephen; Rasooli, Amirhossein (Frontiers in Education, 2019)
Research has consistently demonstrated that teachers’ assessment actions have a significant influence on students’ learning experience and achievement. While much of the assessment research to date has investigated teachers’ understandings of assessment purposes, their developing assessment literacy, or specific classroom assessment practices, few studies have explored teachers’ differential responses to specific and common classroom assessment scenarios. Drawing on a contemporary view of assessment literacy, and providing empirical evidence for assessment literacy as a differential and situated professional competency, the purpose of this study is to explore teachers’ approaches to assessment more closely by examining their differential responses to common classroom assessment scenarios. By drawing on data from 453 beginning teachers who were asked to consider their teaching context and identify their likely actions in response to common assessment scenarios, this paper makes a case for a situated and contextualized view of assessment work, providing an empirically-informed basis for reconceptualizing assessment literacy as negotiated, situated, and differential across teachers, scenarios, and contexts. Data from survey that presents teachers with assessment scenarios are analyzed through descriptive statistics and significance testing to observe similarities and differences by scenario and by participants' teaching division (i.e., elementary and secondary). The paper concludes by considering implications for assessment literacy theory and future related research.